2010
DOI: 10.1192/bjp.bp.109.065490
|View full text |Cite
|
Sign up to set email alerts
|

Autism, ethnicity and maternal immigration

Abstract: Maternal immigration is associated with substantial increased risk of autism-spectrum disorders with differential risk according to different region of birth and possibly ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
3
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 36 publications
(69 reference statements)
7
99
3
8
Order By: Relevance
“…247 In particular, maternal minority ethnic status, such as Aboriginal status, was associated with reduced ASD diagnosis in offspring 102,119,172,243 with an OR ranging from 0.33 to 0.83 for certain non-White ethnic groups compared to White, non-Hispanic people. Furthermore, children who were Black, Hispanic or Folic acid 2 1…”
Section: Ethnicitymentioning
confidence: 99%
See 2 more Smart Citations
“…247 In particular, maternal minority ethnic status, such as Aboriginal status, was associated with reduced ASD diagnosis in offspring 102,119,172,243 with an OR ranging from 0.33 to 0.83 for certain non-White ethnic groups compared to White, non-Hispanic people. Furthermore, children who were Black, Hispanic or Folic acid 2 1…”
Section: Ethnicitymentioning
confidence: 99%
“…Two studies showed that autism births occur in geographical clusters, which could indicate that local factors are involved in the prevalence. 247,256 Another study found that while electromagnetic radiation has been hypothesized to be a risk factor due to biological plausibility, no epidemiological evidence is yet available. 257 Other studies have found no significant association between prenatal exposure to ultrasound and ASD.…”
Section: Othermentioning
confidence: 99%
See 1 more Smart Citation
“…This fact has gained paramount attention by the research community placing Sweden on the 10th place of the top 25 countries that published ASD research between 1980 and 2010 (Office of Autism Research Coordination [OARC] 2012). Moreover, Sweden-based ASD researchers were among the first in Europe and in Nordic countries who began studying possible associations between ethnicity, immigration, and potential risks for ASD among children of immigrant parents (Keen et al 2010), with the scientific report published as early as 1987 (Gillberg et al 1987). This emphasis on cultural variables points to researchers' recognition of the importance of studying these variables for the development of comprehensive supports and services for culturally diverse children with ASD and their families in Sweden (Barnevik-Olsson et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Gardener et al has suggested that human migration is a risk factor for autism and this theory has been confirmed by others [85][86][87][88]. It has been theorized conditions in the countries of origin and the attempts to cope with Western society are stressful.…”
Section: Environmental Factorsmentioning
confidence: 57%